Influence of emulsification mode, stirring speed and volume on ibuprofen-loaded PLGA microparticles - Pavelková, Martina Holická Jan Muselík Kateřina Kubová Veronika Deáková Sylvie Pavloková Miroslava; Vysloužil, Josef Mašek David Vetchý Jakub (Ceska a Slovenska farmacie, 2021)
Microparticles based on biodegradable synthetic lactic acid and glycolic acid copolymer (PLGA) were successfully prepared by the solvent evaporation method. Ibuprofen was chosen as the model drug. Various formulation and process parameters have been used to prepare each sample with emphasis on size reduction. The effect of the emulsification method (direct emulsification or emulsification using an ULTRA-TURRAX or a NE-1000 dispenser), the volume of the aqueous phase (200, 800 ml) and the stirring speed of the emulsion system (600, 1000 rpm) on the characteristic properties of microparticles, such as encapsulation efficiency, drug loading and particle morphology, was observed. The resulting microparticles were evaluated by optical microscopy or laser diffraction and the dissolution test was performed. It was found that the sample prepared by direct emulsification with 800 ml of an aqueous phase at 600 rpm provided the most favorable results, meanwhile the emulsification pre-step using a homogenizer caused promising particle size reduction. Gradual emulsification was evaluated as inapplicable due to great losses. Key words: microparticles solvent evaporation PLGA ibuprofen size reduction.
Keywords: Ibuprofen; Polylactic Acid-Polyglycolic Acid Copolymer; solvent evaporation; PLGA; ibuprofen; velikost částic; kopolymer kyseliny glykolové a mléčné; Microspheres; size reduction; mikrosféry; kyselina polyglykolová; microparticles; Polyglycolic Acid; Particle Size